Model characteristics of sensorimotor reactions and specific perceptions of wrestlers among different weight categories - Tropin, Y.; Korobeynikov, G.; Curby, D.; Vorontsov, A.; Shatskih, V. (International Journal of Wrestling Science, 2019)
Research has been conducted, in which 24 elite level Greco-Roman wrestlers between 19 and 24 years old took part. For the convenience of analysis wrestlers were divided into 3 wide-ranging weight groups: lightweight (under 70kg); middleweight (from 70kg to 92kg) and heavyweight (over 92kg). Based on the test results, model characteristics of sensorimotor reactions and specific perceptions of elite level wrestlers among different weight groups were developed. It was found. that practicing wrestling forms an ability to quickly analyze, assess and predict situations to make right decision in due time during wrestling bout, which explains unreliable differences (p>0.05) in the majority of psychophysiological indicators of the studied athletes.